Do Christian Denominations Exhibit Higher Rates of Alcohol Consumption?: a Study of Korean American Women in California - Kang Sim, D. Eastern (Journal of religion and health, 2013)
Although Korean American women show high levels of involvement in religious practices and high prevalence of alcohol consumption, no studies have assessed the association between religious denomination and alcohol intake among this group of women. This cross-sectional study examined the associations of religious denomination and religious commitment to alcohol consumption among Korean American women in California. Polychotomous regression models were used to provide estimates of the associations between religious denomination and religious commitment to alcohol consumption. Catholic Korean American women (OR 5.61 P < 0.01) and Independent Christian women (OR 4.87 P < 0.01) showed stronger associations to heavy alcohol consumption when compared to Conservative Christian Korean American women. Path analysis suggested that specific denominations had both direct and indirect effects on the outcome of interest, and that religious commitment and drinking models served as moderators for this phenomenon.